A Cloud of Controversy: George Washington and Smallpox Inoculation During the American Revolution - Harris, Madison (URJ-UCCS: Undergraduate Research Journal at UCCS, 2018)
During the Revolutionary War, smallpox wreaked havoc on the American Army in their fight for Independence against the British troops. As John Adams said in a letter to his wife, Abigail Adams, “I mean, the Prevalence of small Pox among our Troops… This fatal Pestilence completed our Destruction.” John Adams, as a confidant to General George Washington understood that this deadly disease was hurting the Army more than the British, Canadians, and Indians combined. Acknowledging this, George Washington made the bold decision: to have the troops undergo mass small pox inoculations. This article will explore George Washington’s highly controversial order to inoculate his soldiers at a pivotal point during the American Revolution. Drawing from multiple primary sources including soldier’s accounts of the horrors of smallpox, John Adam’s letters, and newspapers around the 1770’s, this paper will reflect on the deadly nature of the smallpox disease, the risk and reward factors in undergoing the smallpox inoculation, and the overall effects on the war effort.